Perception of Climate Change of Secondary Level Students in Mechinagar, Jhapa, Nepal - Bhattarai, Charan; Maskey Byanju, Rejina (Perspectives on Higher Education, 2025)
The understanding of climate change among youth is essential for influencing future action. This study assessed climate change understanding, issues, believed consequences, and reported actions among 95 secondary school students in Mechinagar, Jhapa, Nepal, through a survey, and studied 40 years (1982-2022) of local temperature and precipitation data applying Mann-Kendall, Sen's Slope, and additional statistical methods. Results showed very high student awareness (95%) and concern (70.5% "very serious") over climate change, mostly attributable to human actions (80%). Significant school-level participation in mitigation activities (85%) indicated that students were very willing to take action in response to perceived heightened local consequences, such as sudden temperature fluctuations (72%), and heavy rainfall (36%). Meteorological analysis indicated a statistically significant increase in annual rainfall (+24.89 mm/year, p<0.001), largely driven by enhanced monsoon precipitation with high variability and short-term persistence. However, over this study period, there was not a significant long-term trend in the yearly mean temperature (p=0.2785). Student’s perceptions differ with regard to long-term temperature increases, but they are consistent with the observed rise in rainfall intensity and variability. These results demonstrate a high level of young involvement, but they also highlight the need for local data-based, nuanced climate education, with a special emphasis on adaption tactics for the hydrological change management of the region.